1991
DOI: 10.1203/00006450-199109000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Angiotensinogen Gene Expression by Glucocorticoids in Fetal Sheep Liver

Abstract: ABSTRACT. The effect of glucocorticoids in regulating liver angiotensinogen gene expression was studied in chronically instrumented fetal sheep during the last trimester of gestation and was compared with the expression of other hepatic genes (prothrombin, factor IX, and albumin). Four sets of twins were studied at 118 d of gestation, and three sets were studied at 138 d of gestation (term, 145 d). One of each set of twins was infused intraperitoneally with cortisol (5 pmol.mL-'.h-') for 48 h, whereas the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
(29 reference statements)
1
12
1
Order By: Relevance
“…One may suggest that cortisol increases the production of angiotensinogen (renin substrate) to prevent changes in plasma A11 levels in face of a decrease in renin production. Previous studies in sheep, however, have shown that fetal cortisol infusion does not produce changes in circulating angiotensinogen (50) and is, in fact, associated with a decrease in liver angiotensinogen mRNA levels (22), in contrast to previous findings in adults (51,52). An alternative hypothesis would be that cortisol infusion in fetal sheep increases converting enzyme activity and consequently the rate of conversion of angiotensin I to AII, as previously suggested (53).…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…One may suggest that cortisol increases the production of angiotensinogen (renin substrate) to prevent changes in plasma A11 levels in face of a decrease in renin production. Previous studies in sheep, however, have shown that fetal cortisol infusion does not produce changes in circulating angiotensinogen (50) and is, in fact, associated with a decrease in liver angiotensinogen mRNA levels (22), in contrast to previous findings in adults (51,52). An alternative hypothesis would be that cortisol infusion in fetal sheep increases converting enzyme activity and consequently the rate of conversion of angiotensin I to AII, as previously suggested (53).…”
Section: Discussioncontrasting
confidence: 54%
“…Indeed, glucocorticoid has been shown to downregulate both AT, and AT2 receptors in pancreatic acinar cells (44) and to produce down-regulation of glomerular A11 receptor in rats (45). Another possibility is that the decreased expression of renal AT, gene as a function of cortisol concentration is indirect and depends on factors interacting with specific DNA sequences on the glucocorticoid regulatory elements, as previously suggested (22,46). One may also speculate that developmental changes in the physiochemical nature of glucocorticoid receptors (47,48) affect the hormonal responsiveness of certain genes during fetal life.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Hematocrit was determined in duplicate using a meter caliper. RIA, previously established in our laboratory, were used to measure plasma cortisol (19) and plasma A11 (20) concentrations and PRA (20,21).…”
Section: Animalsmentioning
confidence: 99%